Ca2+ and Sr2+ co-doped ceria/carbonates nanocomposites for low temperature solid oxide fuel cells: Composite effect - Jaiswal N.; Upadhyay S.; Kumar D.; Parkash O. (My University, 2025)
A series of co-doped ceria based nanocomposites consisting of Ce0.93Ca0.05Sr0.02O1.93 (CC5S2) and binary carbonates mixture Li2CO3–Na2CO3 (LNCO) have been prepared as functional solid electrolytes for low temperature solid oxide fuel cells (LT-SOFCs). All the samples have been characterized with respect to their thermal behavior, phase, microstructure and electrical conductivity. Single phase formation has been confirmed by X-ray diffraction. In the composites, carbonates are present in the amorphous state. Micrographs show the percolative network of both the phases. Impedance analysis has been used to study the conduction mechanism in the composites. A sudden increase in the conductivity has been observed in all the composites. This is attributed to a superionic transition at the interfaces. Conductivity increases with increasing carbonate content. Composition, CC5S2/35LNCO has the highest conductivity, 0.27 S cm−1 at 500 °C with an activation energy of conduction 0.30 eV. A small value of activation energy indicates the interfacial conduction of the ions in the composites. © 2015 Elsevier Ltd and Techna Group S.r.l.